2011
DOI: 10.1007/s10815-011-9629-2
|View full text |Cite
|
Sign up to set email alerts
|

ART, birth defects and subfertility—what should prospective patients be told?

Abstract: To the EditorWe would like to raise some concerns about the methods used to 'adjust' for the effect of subfertility in the metaanalysis of ART and major birth defects in the recent paper by Rimm et al. [1] Having also published a systematic review and meta-analysis of ART and birth defects (BDs) [2], we are concerned both by the methods used and some of the statements made in the Rimm et al. paper.Assumptions underlying the adjustment method:In their recent meta-analysis, Rimm et al.[1] attempt to 'adjust' t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It has been reported that the risk of having an infant with obstructive renal anomaly increased in overweight/obese and sub-fertile women (10). Therefore, application of assisted reproduction techniques due to subfertility was also evaluated in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the risk of having an infant with obstructive renal anomaly increased in overweight/obese and sub-fertile women (10). Therefore, application of assisted reproduction techniques due to subfertility was also evaluated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that obesity and DM prevalence tend to increase globally has aroused suspicion that maternal overnutrition and its metabolic results may cause the formation of a similar negative environment for in utero kidney development (9). It was suggested that risk for having a child with obstructive renal anomaly increased in over-weight/ obese and sub-fertile women (10).…”
Section: Introductionmentioning
confidence: 99%
“…Some meta‐analyses such as those accomplished by Hansen et al in and Rimm et al in have attempted to combine the data from these smaller studies to delineate the true association, but often with mixed and highly contested results (Hansen et al, , ; Rimm et al, ). Two important recent contributions have also been made with regard to the association between ART and congenital anomalies, an Australian study by Davies et al in and another meta‐analysis accomplished by Hansen et al in (Davies et al, ; Hansen et al, ), both of which support an increased contribution of congenital anomalies within the infertility population, especially those who have undergone ART.…”
Section: Introductionmentioning
confidence: 99%
“…
To the Editor Hansen et al [1] are critical of our study, [2] the primary goal of which is to raise awareness of the problem of having normal couples rather than subfertile couples comprise the control groups when estimating the odds of major malformation (MM) in the offspring of assisted reproductive technology (ART) pregnancies.We used only one study to estimate the impact of subfertility. This was because there is only one large study which offers usable data.
…”
mentioning
confidence: 99%